MEDICINAL PLANTS OF THE SHOHIMARDONSOY BASIN (Scientific journal of the Fergana State University, 2026)
This article presents information about the medicinal plants distributed in the flora of the Shohimardonsoy basin and their taxonomic composition. During the research conducted in this area, 340 species of medicinal plants were studied, belonging to 209 genera and 63 families.